THE DEVELOPMENT ON STUDENT’ LEARNING ACHIEVEMENT BY USING TEAM GAMES TOURNAMENT COOPERATIVE TECHNIQUE - SIDAPHONE , Soulinthone; CHANTHAHONG , Khamxay; THONGPADITH, Sonephet (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
The purposes of this research were to 1) Develop of the student’ learning achievement by using team game tournament (TGT) and 2) to study the students’ satisfaction towards the learning development by using TGT Cooperative Technique. The independent study simple were 40 Lao Language-Literature Department Faculty of Education year 2 student, enrolled in second semester of 2015-2016 academic year. and selected by random sampling. This research model is a research and development (R&D). The research instruments used were a set of Lao language management plans (how to different between Lao and Thai local words). The data were analyzed by mean, standard deviation and t–test dependent. The results this research were as follow 1) The student’ learning achievement by using team game tournament (TGT) cooperative technique was significantly higher than that before the learning development, at .05 level. 2) The students’ satisfaction towards the learning development on Lao language management plans (how to different between Lao and Thai local words) by using TGT cooperation technique as a whole, was at the many level.